Cerdà, Paco (2017). Los últimos, voces de la Laponia española - Pérez Platero, Carlos (Documents d'Anàlisi Geogràfica, 2018)
Cerdà, Paco (2017) Los últimos, voces de la Laponia española Logroño: Editorial Pepitas, 163 p. ISBN 978-84-15862-76-5